Kondisi Kerusakan Jalan dengan Metode Nilai International Roughness Index (IRI) dan Surface Distress Index (SDI) pada Ruas Jalan Jambi – Bulian Dikabupaten Muara Jambi - Nainggolan, Candro Wijaya; Yamali, Fakhrul Rozi; Dony, Wari (Universitas Batanghari Jambi, 2025)
A highway is a transportation infrastructure that plays a very important role in traffic flow, so good road pavement design is a necessity that can connect one place to another. This research aims to determine the value of road pavement conditions and compare them based on the IRI method and the SDI method. Data collection using field surveys is carried out through visual observation of road conditions for the SDI method. Apart from that, observations by car are needed as input data for analyzing IRI values using the Roadlab Pro application. The results of the road assessment using the SDI method were 33.33% in good condition, 53.33% in moderate condition and 13.33 in slightly damaged condition. However, on IRI Roadlab Pro for line I 6.67% was in good condition, 80% was in moderate condition and 13.33% was in a slightly damaged condition and line II 6.67% was in good condition, 86.66% was in moderate condition and 6 .67% is in a state of light damage. Road conditions at STA 6+900 – 8+400 from these two methods are recommended using the Surface Distress Index (SDI).